Implementation Activity-Based Costing & Time-Driven Activity-Based Costing: A Systematic Literature Review - Mediaty; Asri Usman; Safa Rifha’atul Mahmuda; Cindy Nur Azaria Mansa; Falih Zaki Sudharma (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the implementation of ABC in the business sector and TDABC in the business and health company sectors. This research was conducted by reviewing the literature contained in various studies on the implementation of Activity-Based Costing (ABC), and namely Time-Driven Activity-Based Costing (TDABC). Based on the literature review conducted in this study, the implementation of Activity-Based Costing (ABC) in the business sector can increase profitability and competitiveness for companies, while the implementation of Time-Driven Activity-Based Costing (TDABC) in the business and health company sector can increase efficiency and make more accurate decisions and the application of TDABC also shows improvements in the weaknesses of the ABC system.